L’opera italiana alla corte di Lisbona tra Sei e Settecento: protagonismo femminile e intrecci politico-culturali - Giuseppina Raggi (Mélanges de la Casa de Velázquez)
The interest in Italian opera at the Portuguese court emerged long before the consolidated view of critical studies that have traditionally identified the beginning of the enjoyment and diffusion of Italian opera in Portugal with the reign of Joseph I (1714 - r. 1750-1777). This essay offers a new contextualisation of the dynamics of the implementation and enjoyment of Italian opera and theatre, highlighting the role played by the Queen of Portugal, Maria Anna of Habsburg (Vienna 1683-Lisbon 1754), consort of John V, and by her female court. The relationship between the architect-scenographer Filippo Juvarra and the Portuguese court is also reconsidered thanks to new iconographic and documentary data, which have made it possible to reconstruct the theatre projects he designed for the court. This has revealed the historical importance of two unrealised marriages between the Royal House of Braganza and the Royal House of Savoy (respectively in 1679-1682 and 1718-1722), which, reconstructed in detail, show the impact of the operas and theatres prepared for these occasions. The protagonism of Maria Anna of Habsburg represents the key element, now highlighted, to understand the development and success of Italian opera in the Iberian Peninsula through the theatrical policies promoted by her sons Joseph I, King of Portugal, and Barbara de Braganza, Queen of Spain.